2011
DOI: 10.1002/sia.3645
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the surface chemistry of carbon fiber and E‐glass composites for improved adhesion

Abstract: The main challenges in the manufacture of composite materials are low surface energy and the presence of silicon-containing contaminants, both of which greatly reduce surface adhesive strength. In this study, carbon fiber (CF) and E-glass epoxy resin composites were surface treated with the Accelerated Thermo-molecular adhesion Process (ATmaP). ATmaP is a multiaction surface treatment process where tailored nitrogen and oxygen functionalities are generated on the surface of the sample through the vaporization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…These effects are necessary to achieve high composite strengths. Mäder et al, 43 Jung et al, 44 and Gilbert et al 45 showed that polarity modified polymer matrices create stronger bonds with inorganic fibers (e.g., glass fiber).…”
Section: Resultsmentioning
confidence: 99%
“…These effects are necessary to achieve high composite strengths. Mäder et al, 43 Jung et al, 44 and Gilbert et al 45 showed that polarity modified polymer matrices create stronger bonds with inorganic fibers (e.g., glass fiber).…”
Section: Resultsmentioning
confidence: 99%
“…5 In contrast, glass typically has a lower surface energy, making it easier to release from the mold aer fabrication. 68 Therefore, the adhesion strength of the hydrogel to the glass surface is low. Similarly, plastics are also a class of materials with low surface energy, 69,70 especially polytetra-uoroethylene, which adhesives nd difficult to adhere to.…”
Section: Intermolecular Forcesmentioning
confidence: 99%
“…Another approach to alter the surface chemistry of the individual parts is postcure processing. Gilbert et al modified the surfaces of carbon fiber and E‐glass epoxy resin composites with an Accelerated Thermo‐molecular adhesion Process (ATmaP) 123 . ATmaP atomizes N‐methylpyrrolidone liquid and then vaporizes it, resulting in a surface reaction that increases the concentration of polar functional groups and also decreases contamination.…”
Section: Polymer Compositesmentioning
confidence: 99%
“…Gilbert et al modified the surfaces of carbon fiber and E-glass epoxy resin composites with an Accelerated Thermo-molecular adhesion Process (ATmaP). 123 ATmaP atomizes N-methylpyrrolidone liquid and then vaporizes it, resulting in a surface reaction that increases the concentration of polar functional groups and also decreases contamination. ToF-SIMS analysis of treated and untreated samples detected approximately 20 distinct mass fragments (positive ion mode).…”
Section: Spectral Analysismentioning
confidence: 99%